Lithium titanate powder, electrode sheet using same, and power storage device

Through the optimization of process parameters and the addition of surface metal elements, characteristic lithium titanic acid powder was prepared, which solved the problems of negative electrode density and high temperature stability in the battery and achieved efficient battery performance.

JP7654971B2Active Publication Date: 2025-04-02UBE CORPORATION
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020207888
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-15
Publication Date
2025-04-02
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the density of the negative electrode and the storage stability and cycle stability during high-temperature operation in the battery, while suppressing gas generation and increased resistance.

Method used

By controlling the process parameters such as raw material mixing ratio, sintering temperature, surface treatment addition amount and heat treatment temperature, specific lithium titanic acid powders are prepared, with metal elements such as manganese and aluminum on the surface, and have specific oil absorption and particle size distribution.

Benefits of technology

The high initial discharge capacity, rate characteristics, electrode density and physical energy density of the battery are achieved, while suppressing gas generation and increase in resistance during high-temperature operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654971000004
    Figure 0007654971000004
  • Figure 0007654971000001
    Figure 0007654971000001
  • Figure 0007654971000002
    Figure 0007654971000002
Patent Text Reader

Abstract

To provide a lithium titanate powder that is used as an electrode material for a power storage device, has excellent initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and can suppress gas generation and resistance increase during high-temperature operation, an electrode sheet using the lithium titanate powder, and a power storage device.SOLUTION: A lithium titanate powder containing Li4Ti5O12 as a main component contains primary particles and secondary particles of lithium titanate, and the oil absorption of 1-methyl-2-pyrrolidone is 71 mL / 100 g or less, and molybdenum (Mo) and aluminum (Al) are present on the surface of the primary particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to lithium titanate powder suitable as an electrode material for electricity storage devices, an electrode sheet using the same, and an electricity storage device. [Background technology]

[0002] In recent years, various materials have been researched as electrode materials for power storage devices. Among them, lithium titanate has attracted attention as an active material for power storage devices in electric vehicles such as HEVs, PHEVs, and BEVs because of its excellent input / output characteristics when used as an active material.

[0003] A high energy density is required for an electric vehicle storage device from the viewpoint of improving fuel efficiency or power consumption. In addition, stability over a wide temperature range is also important. For example, it is not uncommon for the temperature inside a car to reach 60°C or higher in the summer. Therefore, it is required that an electric vehicle storage device does not have any safety problems or performance degradation even at high temperatures. However, it is known that when an electric storage device containing lithium titanate is used for a long period of time at a high temperature of 60°C or higher, it becomes more difficult to maintain storage stability and cycle stability, which causes an increase in the resistance of the battery. In addition, when the battery is repeatedly charged and discharged, the lithium titanate causes an electrochemical side reaction, which decomposes the organic solvent contained in the electrolyte, and may generate gases such as carbon monoxide, carbon dioxide, methane, and hydrogen (hereinafter referred to as decomposition gases). Therefore, there is a need for the development of lithium titanate that suppresses gas generation and resistance increase while maintaining the battery characteristics during high-temperature operation while increasing the energy density of the electric storage device.

[0004] In Patent Document 1, a specific surface area of ​​4 m 2 / g or more, and contains at least one localized element selected from boron (B), Ln (Ln is at least one metal element selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Hb, Er, Tm, Yb, Lu, Y, and Sc), and M1 (M1 is at least one metal element selected from W and Mo), and the localized elements boron (B), Ln, and M1 are localized and present in the vicinity of the surface of the lithium titanate particles constituting the lithium titanate powder. Patent Document 1 discloses a lithium titanate powder that has a large charge / discharge capacity and can suppress the amount of gas generated during high-temperature operation when applied as an electrode material for an electricity storage device.

[0005] Patent Document 2 discloses a lithium titanate powder that is a spherical secondary particle containing fibrous carbon having an average diameter of 5 to 40 nm and an average aspect ratio of 10 to 1000, contains fibrous carbon with an average circularity of 90% or more, and has a specified average compressive strength and 1-methyl-2-pyrrolidone oil absorption of the spherical secondary particles. Patent Document 2 discloses an electricity storage device that has excellent charge / discharge cycle characteristics in a high-temperature environment and generates a small amount of gas after charge / discharge cycles.

[0006] In Patent Document 3, primary particles are aggregated to form spherical secondary particles, the circularity of the particle projection image of the secondary particles and the oil absorption amount are within specific ranges, and the main component is Li 4 / 3 Ti 5 / 3 Patent Document 3 discloses a lithium-titanium composite oxide characterized by being composed of O4. Patent Document 3 discloses a lithium secondary battery that is easy to handle when preparing an electrode and has good coating properties on a current collector, has little expansion of the electrode used, and has excellent characteristics.

[0007] Patent Document 4 discloses a positive electrode material for lithium ion secondary batteries, which comprises spherical granules made of secondary particles in which the carbon is interposed between primary particles of a positive electrode active material having an olivine structure, and non-spherical aggregates in which the carbon is interposed between the primary particles, and in which the mass, particle size, and N-methyl-2-pyrrolidone oil absorption of the covering carbon are specified. Patent Document 4 discloses that a positive electrode material for lithium ion secondary batteries having excellent input / output characteristics and high electrode density can be obtained. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2018 / 110708 [Patent Document 2] International Publication No. 2017 / 047755 [Patent Document 3] JP 2001-192208 A [Patent Document 4] JP 2020-140827 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the energy storage device in which the lithium titanate of Patent Document 1 is applied as the negative electrode material, the amount of gas generated during high-temperature operation can be suppressed in a battery with a large charge / discharge capacity, but when a coated electrode is created, there is a problem that the electrode density is difficult to increase, resulting in a decrease in the energy density of the battery. Note that the advantages of increasing the electrode density include making the battery itself lighter and smaller, thereby decreasing the proportion of the battery in electronic devices and vehicle installations, greatly improving the design freedom of electronic devices, eliminating the need to secure space for batteries in the case of large battery applications, which leads to an increase in energy density per unit volume, leading to an extension of the driving distance of electric vehicles and the securing of installation space for storage batteries, and reducing the contact resistance of the electrodes inside the battery.

[0010] In the lithium titanate powder of Patent Document 2, which contains fibrous carbon and has a specified average compressive strength of spherical secondary particles, it has been confirmed that the cycle characteristics are improved by ensuring the permeability of the non-aqueous electrolyte. However, there is no description of an increase in resistance during long-term storage in a charged state, and it was found that there is an issue in achieving compatibility with volumetric energy density.

[0011] Furthermore, Patent Document 3 does not disclose any information on the increase in resistance during long-term storage in a charged state, and does not disclose any knowledge on compatibility with improved electrode density. Patent Document 4 discloses information on the positive electrode active material, but does not disclose any knowledge on the increase in resistance during long-term cycle gas or storage in a charged state.

[0012] For the reasons described above, in the electricity storage devices using the negative electrode active materials and electrodes described in Patent Documents 1 to 4, it is not possible to simultaneously improve the electrode density of the negative electrode, which is directly linked to the energy density, and suppress gas generation and resistance increase during high-temperature operation.

[0013] Therefore, the present invention aims to provide lithium titanate powder that can be used as an electrode material for an electricity storage device, has excellent initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and can suppress the amount of gas generated and the increase in resistance value during high-temperature operation, an electrode sheet using the same, and an electricity storage device. [Means for solving the problem]

[0014] The present inventors conducted various studies to achieve the above object, and as a result, discovered a lithium titanate powder in which the concentration of a specific metal element on the particle surface and inside the particle is within a specific range and the concentration of a specific metal element is within a specific range by controlling the raw material mixing ratio in the raw material preparation step during the production of the lithium titanate powder, the firing temperature in the firing step, the amount of additives in the surface treatment step, the heat treatment temperature, etc., and which exhibits a specific range of 1-methyl-2-pyrrolidone oil absorption. They discovered that an electricity storage device in which the lithium titanate powder is used as an electrode material is excellent in initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and further, can suppress the amount of gas generation and the increase in resistance value during high-temperature operation, and thus completed the present invention. That is, the present invention relates to the following items.

[0015] (1) Li4Ti5O 12 The lithium titanate powder is mainly composed of the above lithium titanate, characterized in that the lithium titanate powder contains primary particles and secondary particles of lithium titanate, has a 1-methyl-2-pyrrolidone oil absorption of 71 mL / 100 g or less, and has molybdenum (Mo) and aluminum (Al) present on the surfaces of the primary particles.

[0016] (2) The specific surface area of ​​the lithium titanate powder is 6.1 m 2 / g or less.

[0017] (3) The lithium titanate powder according to (1) or (2), characterized in that the particle size D50 of primary particles corresponding to 50% cumulative volume in a volume-based particle size distribution measured by a laser diffraction scattering method is 0.7 μm or more.

[0018] (4) The lithium titanate powder according to any one of (1) to (3), characterized in that the particle size D50 of secondary particles corresponding to a cumulative volume of 50% in a volume-based particle size distribution determined by a laser diffraction scattering method is 11 μm or more.

[0019] (5) An electrode sheet comprising the lithium titanate powder according to any one of (1) to (4).

[0020] (6) An electricity storage device comprising the electrode sheet according to (5). Effect of the Invention

[0021] According to the present invention, it is possible to provide lithium titanate powder suitable as an electrode material for an electricity storage device, which has excellent initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and further has suppressed gas generation and resistance increase during high-temperature operation, an electrode sheet using the same, and an electricity storage device. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 shows an XPS spectrum measuring the valence distribution of Mo contained in lithium titanate powder containing Li4Ti5O12 as the main component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] [Lithium titanate powder of the present invention] The lithium titanate powder of the present invention is Li4Ti5O 12 The lithium titanate powder is mainly composed of lithium titanate, contains primary particles and secondary particles of lithium titanate, has a 1-methyl-2-pyrrolidone oil absorption of 71 mL / 100 g or less, and has Mo and Al present on the surface of the primary particles.

[0024] <Li4Ti5O 12 Lithium titanate powder containing The lithium titanate powder of the present invention is Li4Ti5O 12 The main component is Li4Ti5O within the range in which the effects of the present invention can be obtained. 12 The main component is the diffraction peak of Li4Ti5O measured by X-ray diffraction method. 12 The lithium titanate powder of the present invention has a diffraction peak intensity ratio of 90% or more of the main peak of Li4Ti5O 12 The ratio of the intensity of the main peak of Li4Ti5O is more preferably 92% or more, and further preferably 95% or more. 12 The other components are the sum of the main peak intensity due to the crystalline components and the maximum intensity of the halo pattern due to the amorphous components. In particular, the lithium titanate powder of the present invention is made up of anatase type titanium dioxide, rutile type titanium dioxide, and lithium titanate with a different chemical formula, Li2TiO, due to the raw materials and synthesis conditions during synthesis. 3、 Li 0.6 Ti 3.4 O 8、The lithium titanate powder of the present invention may contain these Li4Ti5O 12 Crystalline components other than Li 0.6 Ti 3.4 The lower the rate of O8 generation, the more the charging characteristics and charge / discharge capacity of the power storage device can be improved. 12 When the main peak intensity of the anatase type titanium dioxide is taken as 100, it is particularly preferable that the sum of the main peak intensity of the anatase type titanium dioxide, the main peak intensity of the rutile type titanium dioxide, and the intensity corresponding to the main peak of Li2TiO3 calculated by multiplying the peak intensity corresponding to the (-133) plane of Li2TiO3 by 100 / 80 is 5 or less. 12 The main peak of Li4Ti5O in ICDD (PDF2010) PDF card 00-049-0207 12 The main peak of anatase titanium dioxide is a peak corresponding to the diffraction peak attributable to the (111) plane (2θ = 18.33) of PDF card 01-070-6826. The main peak of rutile titanium dioxide is a peak corresponding to the diffraction peak attributable to the (110) plane (2θ = 27.44) of PDF card 01-070-7347. The peak corresponding to the (-133) plane of Li2TiO3 is a peak corresponding to the diffraction peak attributable to the (-133) plane (2θ = 43.58) of Li2TiO3 on PDF card 00-033-0831. 0.6 Ti 3.4 The main peak of O8 is the peak corresponding to the diffraction peak attributable to the (101) plane (2θ=19.98) in the PDF card 01-070-2732. Note that "ICDD" is an abbreviation for the International Centre for Diffraction Data, and "PDF" is an abbreviation for Powder Diffraction File.

[0025] <Molybdenum (Mo) and Aluminum (Al) Content> The lithium titanate powder of the present invention contains Mo and Al on the surface of the primary particles. The metal elements contained therein mean that Mo and Al are detected by inductively coupled plasma atomic emission spectrometry (ICP-AES) of the lithium titanate powder of the present invention. The lower limit of the amount detected by inductively coupled plasma atomic emission spectrometry is usually 0.001 mass%.

[0026] <Molybdenum (Mo) and aluminum (Al) content> The content (mass%) of Mo and Al in the lithium titanate powder of the present invention determined by X-ray fluorescence analysis (XRF) is 0.01 or more and 0.8 or less. If the content of each of the metal elements is within this range, an electricity storage device excellent in initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and further suppresses the amount of gas generated and the increase in resistance value during high-temperature operation, can be obtained. More preferably, it is 0.1 or more and 0.6 or less, and even more preferably, it is 0.1 or more and 0.4 or less. The content indicates the proportion of the mass of Mo and Al contained in the total mass of the lithium titanate powder.

[0027] <Mass ratio of molybdenum (Mo) to aluminum (Al) (Mo (mass%) / Al (mass%)> The lithium titanate powder of the present invention contains Mo and Al on the surface of the primary particles, and the mass ratio (Mo (mass %) / Al (mass %)) is 0.01 or more and 80 or less. If the mass ratio is within this range, an electricity storage device excellent in initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and further suppresses the amount of gas generation and the increase in resistance value during high temperature operation, can be obtained. The mass ratio is more preferably 0.2 or more and 6 or less, and even more preferably 0.3 or more and 4 or less.

[0028] In addition, in the lithium titanate powder of the present invention, Mo and Al are contained more on the surface than inside the primary particles of lithium titanate contained in the powder. In a cross-sectional analysis of the primary particles of lithium titanate using a scanning transmission electron microscope, it is sufficient that Mo is contained more in the so-called near-surface region from the surface of the primary particles of lithium titanate to a depth of about 5 nm, and it is sufficient that Al is contained more in the so-called near-surface region from the surface to a depth of about 20 nm, and it is preferable that Mo and Al are not detected at a depth of about 100 nm. It is preferable that Mo and Al are fixed in a state of being chemically bonded to the surface of the primary particles. When Mo and Al are present in such a state, a power storage device is obtained that is excellent in initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and further suppresses the amount of gas generation and the increase in resistance value during high-temperature operation. The lower limit of the detection amount in the measurement by energy dispersive X-ray spectroscopy is usually 0.5 atm%, although the value varies depending on the element and state to be measured. Therefore, at a depth of about 100 nm, Mo and Al may each be detected in a range of 0.5 atm % or less.

[0029] <Inclusion of heterogeneous element M1> The lithium titanate powder of the present invention may contain at least one element selected from B, Mg, Zn, Ga, W, S, or In as a further hetero element (hereinafter referred to as element M1). By containing element M1 together with Mo and Al, the lithium titanate powder of the present invention further improves the efficiency and rate characteristics during high-temperature charge and discharge. Element M1 is preferably sulfur (S). It is presumed that by containing element S together with Mo and Al, the lithium titanate powder of the present invention adjusts the electronic conductivity of the surface of the primary particles of the lithium titanate powder, thereby suppressing the electrical resistance.

[0030] The content (mass%) of element M1 determined by X-ray fluorescence analysis (XRF) is 0.01 to 1.0. From the viewpoint of improving the efficiency and rate characteristics of the electricity storage device during high-temperature charge and discharge, the content is preferably 0.03 to 0.8, and more preferably 0.1 to 0.6. When element M1 is S, the content is preferably 0.1 to 0.5, and more preferably 0.15 to 0.48.

[0031] <1-Methyl-2-pyrrolidone oil absorption> The 1-methyl-2-pyrrolidone (hereinafter sometimes referred to as NMP) oil absorption of the lithium titanate powder of the present invention is 71 ml / 100 g or less. If the NMP oil absorption is within this range, it is possible to obtain an electricity storage device that improves the electrode density, initial discharge capacity, volumetric energy density, and rate characteristics, and suppresses the amount of gas generation and the increase in resistance value during high-temperature operation. It is preferably 70 ml / 100 g, and more preferably 69 ml / 100 g. Here, the unit ml / 100 g represents the amount of NMP absorption (unit is ml) per 100 g of the lithium titanate powder of the present invention. The reason why the above effect can be obtained is not necessarily clear, but it is presumed that NMP is a solvent used for electrode preparation, and by appropriately controlling the NMP oil absorption of the lithium titanate powder, it contributes to efficient adhesion with the negative electrode active material, conductive assistant, and binder, and high-density electrode processability can be realized.

[0032] <Specific surface area> The specific surface area of ​​the lithium titanate powder of the present invention means the adsorption area per unit mass when nitrogen is used as the adsorption gas. The measurement method will be described in the examples below.

[0033] The lithium titanate constituting the lithium titanate powder of the present invention has a specific surface area of ​​6.1 m 2 If the specific surface area of ​​the lithium titanate powder is 6.0 m / g or less, it is possible to obtain an electricity storage device that is excellent in initial discharge capacity, rate characteristics, electrode density, and volumetric energy density, and further suppresses the amount of gas generation and the increase in resistance value during high-temperature operation. 2 / g or less is more preferable, and 5.7m 2 / g or less is more preferable.

[0034] <d50> D50 of the lithium titanate powder of the present invention is an index of the volume median particle size. It means the particle size at which the cumulative volume frequency calculated from the volume fraction determined by laser diffraction / scattering particle size distribution measurement is 50% when calculated from the smallest particle size. The measurement method will be described in the examples below.

[0035] <Primary and secondary particles> The lithium titanate powder of the present invention includes primary particles of lithium titanate and secondary particles formed by aggregation of the primary particles. The primary particles refer to individual particles that constitute the lithium titanate powder and cannot be further divided by a crushing treatment.

[0036] From the viewpoint of improving the electrode density, volumetric energy density, and rate characteristics, the D50 of the secondary particles of the lithium titanate powder of the present invention is 11 μm or more, preferably 12 μm or more, and more preferably 12.4 μm or more. Also, it is 20 μm or less, preferably 18 μm or less, and more preferably 14 μm or less. Note that the D50 of the secondary particles represents the D50 before the disintegration treatment (ultrasonic application by an ultrasonic irradiator).

[0037] From the viewpoint of improving the electrode density, volumetric energy density, and rate characteristics, the D50 of the primary particles of the lithium titanate powder of the present invention is 0.7 μm or more, preferably 0.73 μm or more, and more preferably 0.75 μm or more. Also, it is 3 μm or less, preferably 2 μm or less, and more preferably 1.5 μm or less. The D50 of the primary particles represents the D50 after a crushing treatment using an ultrasonic irradiator. Also, the lithium titanate powder may contain a cumulative volume frequency of primary particles having a primary particle diameter of less than 0.7 μm in the range of 10% to 50%, a cumulative volume frequency of primary particles having a primary particle diameter of less than 0.73 μm in the range of 15% to 55%, and a cumulative volume frequency of primary particles having a primary particle diameter of less than 0.75 μm in the range of 10% to 60%. Furthermore, the cumulative volume frequency of primary particles exceeding 3 μm may be in the range of 50% to 90%, the cumulative volume frequency of primary particles exceeding 2 μm may be in the range of 45% to 85%, and the cumulative volume frequency of primary particles exceeding 1.5 μm may be in the range of 40% to 80%.

[0038] <ph> In the lithium titanate powder of the present invention, the pH is preferably 10.0 to 11.5, more preferably 10.5 to 11.4, and even more preferably 10.7 to 11.3. Within this range, an electricity storage device can be obtained in which the amount of gas generated and the increase in resistance value during high-temperature operation are suppressed without impairing the electrode density and rate characteristics of the electricity storage device. Although this is only speculation, it is assumed that the pH of the lithium titanate powder of the present invention is influenced by the surface state, particularly the valence of molybdenum. The pH in the present invention refers to a value measured by dissolving the lithium titanate powder in water.

[0039] <Molybdenum (Mo) valence> In the manufacturing method described in the specification of Patent Document 1, the valence of Mo is not specified. According to X-ray photoelectron spectroscopy (XPS) of the lithium titanate primary particles contained in the lithium titanate powder of the present invention, the ratio of the peak area of ​​Mo (pentavalent and tetravalent) to the total peak area derived from Mo (hexavalent, pentavalent and tetravalent) is preferably 30% or less, more preferably 20% or less. If the ratio of the peak area of ​​Mo (pentavalent and tetravalent) is 30% or less, side reactions of Mo are suppressed during the initial charge and discharge, and an electricity storage device excellent in initial discharge capacity, rate characteristics, electrode density and volumetric energy density, and further suppressed gas generation amount and resistance value increase during high temperature operation, can be obtained.

[0040] The reason why the amount of gas generated and the increase in resistance are suppressed is unclear, but it is thought that the presence of Mo at the interface between the lithium titanate particle surface and the non-aqueous electrolyte (including solid electrolyte) allows Mo to efficiently convert decomposition products generated on the particle surface into other substances, suppressing the overall increase in gas generation and resistance components. In addition, the formation of a Mo diffusion layer on the lithium titanate particle surface prevents the decomposition of the electrolyte, Li4Ti5O 12 It is believed that the amount of gas generated due to decomposition of the electrolyte can be further suppressed by protecting the active sites of the electrolyte.

[0041] <Periodic table> The periodic table in the present invention refers to a long-form periodic table of elements based on the provisions of IUPAC (International Union of Pure and Applied Chemistry).

[0042] [Method of manufacturing the lithium titanate powder of the present invention] An example of the method for producing lithium titanate powder of the present invention will be described below, divided into a raw material preparation step, a firing step, and a surface treatment step, but the method for producing lithium titanate powder of the present invention is not limited thereto.

[0043] <Raw material preparation process> The raw materials for the lithium titanate powder of the present invention are composed of a titanium raw material and a lithium raw material. Titanium compounds such as anatase type titanium dioxide and rutile type titanium dioxide are used as the titanium raw material. It is preferable that the titanium raw material reacts easily with the lithium raw material in a short time, and from that viewpoint, anatase type titanium dioxide is preferable. In order to sufficiently react the raw materials by firing for a short time, the D50 of the titanium raw material is preferably 5 μm or less.

[0044] As the lithium source, lithium compounds such as lithium hydroxide monohydrate, lithium oxide, lithium hydrogen carbonate, and lithium carbonate are used.

[0045] As for the charge ratio of the titanium raw material and the lithium raw material, the atomic ratio Li / Ti of Li to Ti is preferably 0.81 or more, more preferably 0.83 or more, because a small charge ratio may promote the generation of a specific impurity phase in the lithium titanate powder obtained after firing, which may adversely affect the battery characteristics.

[0046] In the present invention, when the mixture of the above raw materials is fired in a short time, it is preferable to prepare the mixed powder constituting the mixture before firing so that D95 in the particle size distribution curve measured by a laser diffraction / scattering type particle size distribution analyzer is 5 μm or less. Here, D95 is the particle size at which the cumulative volume frequency calculated by volume fraction is 95% when integrated from the smallest particle size.

[0047] The following methods can be used to prepare the mixture. The first method is to mix the raw materials, then mix and pulverize them at the same time. The second method is to pulverize the raw materials until the D95 after mixing is 5 μm or less, and then mix them or mix them while lightly pulverizing them. The third method is to produce powders consisting of fine particles from the raw materials by a method such as crystallization, classify them as necessary, and mix them or mix them while lightly pulverizing them. Among them, in the first method, the method of mixing the raw materials and pulverizing them at the same time is an industrially advantageous method because it requires fewer steps. A conductive agent may also be added at the same time.

[0048] In any of the first to third methods, the method of mixing the raw materials is not particularly limited, and may be either wet mixing or dry mixing. For example, a Henschel mixer, an ultrasonic dispersing device, a homomixer, a mortar, a ball mill, a centrifugal ball mill, a planetary ball mill, a vibration ball mill, an attritor type high speed ball mill, a bead mill, a roll mill, etc. may be used.

[0049] When the mixture obtained by any one of the first to third methods is a mixed powder, it can be directly subjected to the next firing step. When the mixture is a mixed slurry consisting of the mixed powder, it can be directly subjected to the next firing step after being dried by a rotary evaporator or the like. When firing is performed using a rotary kiln, the mixed slurry can be directly subjected to the furnace.

[0050] <Firing process> Next, the mixture obtained is fired. From the viewpoint of increasing the specific surface area of ​​the powder obtained by firing, increasing the crystallite size and the primary particle size of the powder, and reducing the amount of impurities derived from the furnace tube, it is preferable to fire at a high temperature for a short time. From this viewpoint, the maximum temperature during firing is preferably 1100°C or less, more preferably 1000°C or less, and even more preferably 960°C or less. From the viewpoint of reducing the ratio of specific impurity phases and increasing the crystallinity of lithium titanate, the maximum temperature during firing is preferably 800°C or more, more preferably 810°C or more. Similarly, from the above viewpoint, the holding time at the maximum temperature during firing is preferably 2 minutes to 60 minutes, more preferably 5 minutes to 45 minutes, and even more preferably 5 minutes to 30 minutes. When the maximum temperature during firing is high, it is preferable to select a shorter holding time. Similarly, from the viewpoint of increasing the crystallite size obtained by firing, it is preferable to particularly shorten the residence time at 700°C to 800°C during the temperature rise process during firing, for example, within 15 minutes.

[0051] The firing method is not particularly limited as long as it can be performed under the above conditions. Examples of firing methods that can be used include fixed bed firing furnaces, roller hearth firing furnaces, mesh belt firing furnaces, fluidized bed firing furnaces, and rotary kiln firing furnaces. However, in order to perform efficient firing in a short time, roller hearth firing furnaces, mesh belt firing furnaces, and rotary kiln firing furnaces are preferred. When using a roller hearth firing furnace or mesh belt firing furnace in which the mixture is placed in a sagger and fired, it is preferable to keep the amount of the mixture placed in the sagger small in order to ensure uniformity in the temperature distribution of the mixture during firing and to obtain a constant quality of lithium titanate.

[0052] A rotary kiln-type firing furnace is particularly preferred for producing the lithium titanate powder of the present invention because it does not require a container for containing the mixture, the mixture can be continuously fed into the firing furnace, the thermal history of the fired material is uniform, and homogeneous lithium titanate can be obtained.

[0053] The atmosphere during firing is not particularly limited, regardless of the firing furnace, as long as it can remove the desorbed moisture and carbon dioxide gas. Usually, an air atmosphere using compressed air is used, but an oxygen, nitrogen, or hydrogen atmosphere may also be used.

[0054] Although the lithium titanate powder after firing has slight agglomeration, it is not necessary to perform pulverization to destroy the particles, and therefore, after firing, it is sufficient to perform disintegration or classification to the extent that disintegration is broken down as necessary. If disintegration is performed only to the extent that disintegration is broken down without pulverization, the high crystallinity of the lithium titanate powder after firing is maintained even after that.

[0055] <Surface treatment process> The lithium titanate powder of the present invention is a lithium titanate powder containing molybdenum and aluminum, and when used as an electrode material for an electricity storage device, it can provide an effect of suppressing gas generation and an increase in resistance value during high-temperature operation. The lithium titanate powder of the present invention can be produced by adding a compound containing molybdenum and aluminum (hereinafter, sometimes referred to as a treatment agent) in the firing step, but more preferably, the lithium titanate powder of the present invention can be produced by the following surface treatment step or the like.

[0056] The lithium titanate powder before surface treatment obtained by the above steps (hereinafter may be referred to as the base lithium titanate powder. Also, hereinafter, the lithium titanate particles constituting the base lithium titanate powder may be referred to as the base lithium titanate particles) is mixed with treatment agent 1 and treatment agent 2, and is preferably heat-treated.

[0057] The compound containing molybdenum (treatment agent 1) is not particularly limited, but examples thereof include oxides, hydroxides, sulfate compounds, nitrate compounds, fluorides, organic compounds, and metal salt compounds containing molybdenum. Specific examples thereof include molybdenum oxide, molybdenum trioxide, molybdenum trioxide hydrate, molybdenum boride, molybdophosphoric acid, molybdenum disilicide, molybdenum chloride, molybdenum sulfide, molybdosilicic acid hydrate, sodium molybdenum oxide, molybdenum carbide, molybdenum acetate dimer, lithium molybdate, sodium molybdate, potassium molybdate, calcium molybdate, magnesium molybdate, manganese molybdate, and ammonium molybdate. In order to uniformly diffuse molybdenum on the particle surface of lithium titanate powder, it is suitable to use the wet method described below. In this case, it is preferable to dissolve a molybdenum-containing compound that is soluble in a solvent in the solvent and mix it with the lithium titanate powder of the base material. In terms of suppressing the amount of gas generation, lithium molybdate containing molybdenum is preferable. Regarding the valence of molybdenum, even if it is added in a hexavalent state as a raw material, it is assumed that when chemical bonds are formed on the LTO surface or inside the crystal, dangling bonds exist and the valence is partially 4 to 5.

[0058] The amount of the molybdenum-containing compound (treatment agent 1) added may be any amount as long as the molybdenum content in the lithium titanate powder falls within the range of the present invention. For example, when lithium molybdate (Li2MoO4) is used as treatment agent 1, from the viewpoints of achieving excellent initial discharge capacity, rate characteristics, electrode density, and volumetric energy density of the power storage device and suppressing the amount of gas generated and increase in resistance value during high-temperature operation, treatment agent 1 may be added to the lithium titanate powder of the base material in a ratio of 0.12 mmol / LTO100 g to 28.8 mmol / LTO100 g, more preferably 0.5 mmol / LTO100 g to 15.5 mmol / LTO100 g, and particularly preferably 1.0 mmol / LTO100 g to 10.0 mmol / LTO100 g.

[0059] The aluminum-containing compound (treatment agent 2) is not particularly limited, but examples thereof include molybdenum oxides, hydroxides, sulfate compounds, nitrate compounds, fluorides, organic compounds, and metal salt compounds containing molybdenum.Specific examples of Al-containing compounds include aluminum acetate, aluminum fluoride, and aluminum sulfate.Among these, aluminum sulfate, its hydrate, and aluminum fluoride are preferred.

[0060] The amount of the aluminum-containing compound (treatment agent 2) added may be any amount as long as the content of molybdenum in the lithium titanate powder falls within the range of the present invention. For example, when aluminum sulfate·14-18 hydrate (Al2(SO4)3·14-18H2O) is used, from the viewpoints of achieving excellent initial discharge capacity, rate characteristics, electrode density, and volumetric energy density of the power storage device and suppressing the amount of gas generation and increase in resistance value during high-temperature operation, treatment agent 2 may be added to the lithium titanate powder substrate in a ratio of 0.16 mmol / LTO100 g to 63.5 mmol / LTO100 g, more preferably 3.2 mmol / LTO100 g to 31.7 mmol / LTO100 g, and particularly preferably 4.0 mmol / LTO100 g to 15.9 mmol / LTO100 g.

[0061] There are no particular limitations on the method of mixing the lithium titanate powder base material with the molybdenum-containing compound (treatment agent 1), the aluminum-containing compound (treatment agent 2), and even the compound containing element M (treatment agent 3), and either wet mixing or dry mixing can be used. However, it is preferable to uniformly disperse the molybdenum-containing compound (treatment agent 1) or the aluminum-containing compound (treatment agent 2) on the surface of the lithium titanate particles base material, and from that point of view, wet mixing is preferred.

[0062] For dry mixing, for example, a paint mixer, a Henschel mixer, an ultrasonic dispersing device, a homomixer, a mortar, a ball mill, a centrifugal ball mill, a planetary ball mill, a vibrating ball mill, an attritor type high speed ball mill, a bead mill, a roll mill, etc. can be used.

[0063] In the wet mixing, treatment agent 1, treatment agent 2, and the lithium titanate powder of the substrate are added to a water or alcohol solvent and mixed in a slurry state. As the alcohol solvent, those with a boiling point of 100°C or less, such as methanol, ethanol, and isopropyl alcohol, are preferred because they are easy to remove. Also, from an industrial perspective, water solvents are preferred because they are easy to recover and dispose of.

[0064] The amount of the solvent is not a problem as long as the treatment agent 1, the treatment agent 2, and the lithium titanate particles of the substrate are sufficiently wetted, but it is preferable that the treatment agent 1, the treatment agent 2, and the lithium titanate particles of the substrate are uniformly dispersed in the solvent, and for this purpose, the amount of the treatment agent 1 or the treatment agent 2 dissolved in the solvent is preferably 50% or more of the total amount of the treatment agent 1 or the treatment agent 2 put into the solvent. Since the amount of the treatment agent 1 or the treatment agent 2 dissolved in the solvent increases as the temperature increases, it is preferable to mix the lithium titanate powder of the substrate and the treatment agent 1 or the treatment agent 2 in the solvent while heating. Furthermore, since the amount of the solvent can be reduced by heating, the method of mixing while heating is suitable for industrial use. The temperature during mixing is preferably 40°C to 100°C, more preferably 60°C to 100°C.

[0065] In the case of wet mixing, although it depends on the heat treatment method, it is preferable to remove the solvent before the heat treatment performed after the mixing process. When removing the solvent, it is difficult to control the specific specific surface area and D50 of the primary particles and secondary particles by simply evaporating the solvent to dryness. Methods for evaporating the solvent to dryness include a method of heating and evaporating the slurry while stirring with a stirring blade, a method using a drying device that can dry while stirring, such as a conical dryer, and a method using a spray dryer, but the method using a spray dryer is preferable. The reason is that, unlike conventional evaporation to dryness, the conditions of the spray dryer greatly affect the secondary particle morphology and the surface treatment process. The drying temperature of the spray dryer is preferably 180°C to 300°C, more preferably 200°C to 270°C, and even more preferably 215°C to 270°C. Since the powder property range of the secondary particles varies depending on the specific condition of the drying temperature, it is possible to increase the initial discharge capacity, rate characteristics, electrode density, and volumetric energy density.

[0066] It is preferable to perform heat treatment after mixing the lithium titanate powder of the substrate with the treatment agent 1 and further with the treatment agent 2. The heat treatment temperature is a temperature at which molybdenum or further element M diffuses into at least the surface region of the lithium titanate particles of the substrate, and at which the specific surface area does not decrease significantly due to sintering of the lithium titanate of the substrate. The upper limit of the heat treatment temperature is preferably 700°C or less, more preferably 600°C or less. The lower limit of the heat treatment temperature is preferably 300°C or more, more preferably 400°C or more. The heat treatment time is preferably 0.1 to 8 hours, more preferably 1 to 5 hours. The temperature and time at which the element M diffuses into at least the surface region of the lithium titanate particles of the substrate are appropriately set because the reactivity differs depending on the compound containing the element M.

[0067] The heating method in the heat treatment is not particularly limited. Examples of heat treatment furnaces that can be used include fixed bed type firing furnaces, roller hearth type firing furnaces, mesh belt type firing furnaces, fluidized bed type firing furnaces, and rotary kiln type firing furnaces. The atmosphere during the heat treatment may be either an air atmosphere or an inert atmosphere such as a nitrogen atmosphere. When a metal salt compound containing molybdenum or element M is used as the compound containing molybdenum or element M (treatment agent 2), an air atmosphere is preferred in which anion species are easily removed from the particle surface.

[0068] The lithium titanate powder obtained after the heat treatment as described above has some degree of agglomeration, but does not need to be pulverized to destroy the particles. Therefore, after the heat treatment, it is sufficient to perform crushing or classification to the extent that agglomerations are broken down as necessary.

[0069] The lithium titanate powder of the present invention may be mixed with a treatment agent in a surface treatment step, granulated, and heat-treated to form a powder containing secondary particles formed by aggregation of primary particles. Any method for granulation may be used as long as secondary particles can be formed, but a spray dryer is preferred because it can process large quantities.

[0070] In order to reduce the amount of moisture contained in the lithium titanate powder of the present invention, dew point control may be performed in the heat treatment process. If the heat-treated powder is exposed to the air as it is, the amount of moisture contained in the powder will increase, so it is preferable to handle the powder in a dew point controlled environment during cooling in the heat treatment furnace and after the heat treatment. The heat-treated powder may be classified as necessary to make the particles within the desired maximum particle size range. When dew point control is performed in the heat treatment process, it is preferable to seal the lithium titanate powder of the present invention in an aluminum laminate bag or the like and then place it in an environment outside of dew point control. Even under dew point control, if the lithium titanate powder after heat treatment is pulverized, moisture is easily absorbed from the crushed surface, and the amount of moisture contained in the powder increases, so it is preferable not to pulverize it when heat treatment is performed. As for the heat treatment conditions, the temperature and holding time in a specific range greatly affect the secondary particle morphology and the surface treatment process. The heat treatment temperature is preferably 450°C or higher, and preferably less than 550°C. This is because if the heat treatment temperature exceeds 550°C, the specific surface area is significantly reduced, and the battery performance, especially the rate characteristics, is significantly reduced. Furthermore, the holding time is preferably 11 hours or longer, because if the heating time is short, not only will the amount of moisture in the powder increase, but it is also thought to affect the state of the particle surfaces.

[0071] [Active material] The active material used in the electrode sheet of the present invention contains the lithium titanate powder of the present invention. It may contain one or more substances other than the lithium titanate powder of the present invention. Examples of other substances include carbon materials (pyrolytic carbons, cokes, graphites (artificial graphite, natural graphite, etc.), organic polymer compound combustion bodies, carbon fibers), tin and tin compounds, silicon and silicon compounds.

[0072] [Electricity storage device] The electricity storage device of the present invention is a device that includes an electrode containing the active substance material of the present invention and stores and releases energy by utilizing the intercalation and deintercalation of lithium ions into such an electrode, and examples of such a device include a hybrid capacitor and a lithium battery.

[0073] [Hybrid capacitor] The hybrid capacitor is a device that uses an active material such as activated carbon, which forms a capacitance by physical adsorption similar to the electrode material of an electric double layer capacitor, an active material such as graphite, which forms a capacitance by physical adsorption and intercalation / deintercalation, or an active material such as a conductive polymer, which forms a capacitance by redox, in the positive electrode, and the active material of the present invention in the negative electrode. The active material of the present invention is usually used in the form of an electrode sheet of the hybrid capacitor.

[0074] [Lithium battery] The lithium battery of the present invention is a general term for lithium primary batteries and lithium secondary batteries. In this specification, the term lithium secondary battery is used as a concept including so-called lithium ion secondary batteries and all-solid-state lithium secondary batteries.

[0075] The lithium battery is composed of a positive electrode, a negative electrode, and a non-aqueous electrolyte in which an electrolyte salt is dissolved in a non-aqueous solvent, or a solid electrolyte, and the active material of the present invention can be used as an electrode material. The active material of the present invention is usually used in the form of an electrode sheet for the lithium battery. This active material may be used as either a positive electrode active material or a negative electrode active material, but the following description will be given of the case where it is used as a negative electrode active material.

[0076] <Negative electrode> The negative electrode has a mixture layer containing a negative electrode active material (the active material of the present invention), a conductive agent, and a binder on one or both sides of a negative electrode current collector. This mixture layer is usually in the form of an electrode sheet. In the case of a negative electrode current collector having pores such as a porous body, the mixture layer contains a negative electrode active material (the active material of the present invention), a conductive agent, and a binder in the pores. When this mixture layer is used in an all-solid-state battery, the mixture layer may further contain a solid electrolyte material.

[0077] The conductive agent for the negative electrode is not particularly limited as long as it is an electron conductive material that does not undergo chemical changes. For example, graphites such as natural graphite (e.g., flake graphite) and artificial graphite, carbon blacks such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes such as single-phase carbon nanotubes, multi-walled carbon nanotubes (graphite layers are multi-layered concentric cylinders) (non-fishbone-shaped), cup-stacked carbon nanotubes (fishbone-shaped), nodular carbon nanofibers (non-fishbone structure), and platelet-type carbon nanofibers (playing cards), etc. may be used in combination with graphites, carbon blacks, and carbon nanotubes. Although not particularly limited, the specific surface area of ​​the carbon blacks is preferably 30 m 2 / g~3000m 2 / g, and more preferably 50m 2 / g~2000m 2 The specific surface area of ​​the graphite is preferably 30 m 2 / g~600m 2 / g, and more preferably 50m 2 / g~500m 2 The aspect ratio of the carbon nanotubes is 2-150, preferably 2-100, and more preferably 2-50.

[0078] The amount of conductive agent added should be optimized because it varies depending on the specific surface area of ​​the active material and the type and combination of conductive agents, but is preferably 0.1% by mass to 10% by mass, and more preferably 0.5% by mass to 5% by mass in the mixture layer. If it is less than 0.1% by mass, the conductivity of the mixture layer cannot be ensured, and if it exceeds 10% by mass, the active material ratio decreases, and the discharge capacity of the electricity storage device per unit mass and unit volume of the mixture layer becomes insufficient, which is not suitable for increasing the capacity.

[0079] Examples of the binder for the negative electrode include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), styrene-butadiene copolymer (SBR), acrylonitrile-butadiene copolymer (NBR), and carboxymethyl cellulose (CMC). Although not particularly limited, the molecular weight of polyvinylidene fluoride is preferably 20,000 to 1,000,000. From the viewpoint of ensuring the binding property of the mixture layer, it is preferably 25,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more. From the viewpoint of ensuring conductivity without interfering with the contact between the active material and the conductive agent, it is preferably 500,000 or less. In particular, when the specific surface area of ​​the active material is 10 m 2 In the case where the molecular weight is 1 / g or more, the molecular weight is preferably 100,000 or more.

[0080] The amount of binder added should be optimized since it varies depending on the specific surface area of ​​the active material and the type and combination of conductive agents, but is preferably 0.2% by mass to 15% by mass in the mixture layer. From the viewpoint of increasing the binding property and ensuring the strength of the mixture layer, it is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more. From the viewpoint of preventing a decrease in the active material ratio and a decrease in the discharge capacity of the electricity storage device per unit mass and unit volume of the mixture layer, it is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0081] Examples of the negative electrode current collector include aluminum, stainless steel, nickel, copper, titanium, baked carbon, or those coated with carbon, nickel, titanium, or silver. The surface of these materials may be oxidized, or the surface of the negative electrode current collector may be roughened by surface treatment. Examples of the form of the negative electrode current collector include a sheet, net, foil, film, punched, lath, porous body, foam, fiber group, and nonwoven fabric molded body. Porous aluminum is preferred as the form of the negative electrode current collector. The porosity of the porous aluminum is 80% or more and 95% or less, and preferably 85% or more.

[0082] The negative electrode can be produced by uniformly mixing the negative electrode active material (including the active material of the present invention), the conductive agent, and the binder in a solvent to prepare a paint, which is then applied to the negative electrode current collector, dried, and compressed. In the case of a negative electrode current collector having pores, such as a porous body, the paint is pressed into the pores of the current collector to fill the pores, or the current collector having pores is immersed in the paint to diffuse the pores, and then dried and compressed.

[0083] As a method for uniformly mixing the negative electrode active material (the active material of the present invention), the conductive agent, and the binder in a solvent to prepare a paint, for example, a kneader of the type in which a stirring rod revolves while rotating in a kneading vessel such as a planetary mixer, a twin-screw extrusion type kneader, a planetary stirring defoamer, a bead mill, a high-speed rotating type mixer, a powder suction continuous dissolution and dispersion device, etc. Also, as a manufacturing process, the process may be divided according to the solid content concentration, and these devices may be used separately.

[0084] In order to mix the negative electrode active material (the active material of the present invention), the conductive agent and the binder uniformly in the solvent, the mixing should be optimized because it depends on the specific surface area of ​​the active material, the type of conductive agent, the type of binder and the combination of these. However, when using a kneader in which the stirring rod revolves while rotating in a kneading container such as a planetary mixer, a twin-screw extrusion type kneader, a planetary stirring degassing device, etc., it is preferable to divide the steps according to the solid content concentration in the manufacturing process, knead the mixture in a state where the solid content concentration is high, and then gradually reduce the solid content concentration to adjust the viscosity of the paint. The high solid content concentration is preferably 60% by mass to 90% by mass, more preferably 60% by mass to 80% by mass. If it is 60% by mass or more, it is preferable because shear force can be obtained, if it is 90% by mass or less, it is preferable because the load on the device is reduced, and if it is 80% by mass or less, it is more preferable.

[0085] The mixing procedure is not particularly limited, but examples thereof include a method of simultaneously mixing the negative electrode active material, the conductive agent, and the binder in a solvent, a method of previously mixing the conductive agent and the binder in a solvent and then adding and mixing the negative electrode active material, a method of previously preparing a negative electrode active material slurry, a conductive agent slurry, and a binder solution, and then mixing each of them, etc. Among these, in order to disperse them uniformly, a method of previously mixing the conductive agent and the binder in a solvent and then adding and mixing the negative electrode active material, and a method of previously preparing a negative electrode active material slurry, a conductive agent slurry, and a binder solution, and then mixing each of them are preferred.

[0086] As the solvent, an organic solvent can be used. Examples of the organic solvent include aprotic organic solvents such as 1-methyl-2-pyrrolidone, dimethylacetamide, and dimethylformamide, which may be used alone or in combination of two or more kinds, and preferably 1-methyl-2-pyrrolidone.

[0087] When an organic solvent is used as the solvent, it is preferable to dissolve the binder in the organic solvent before use.

[0088] <Positive electrode> The positive electrode has a mixture layer containing a positive electrode active material, a conductive agent, and a binder on one or both sides of a positive electrode current collector.

[0089] As the positive electrode active material, a material capable of absorbing and releasing lithium is used. For example, the active material may be a composite metal oxide containing lithium and containing cobalt, manganese, or nickel, or a lithium-containing olivine-type phosphate. These positive electrode active materials may be used alone or in combination of two or more. Examples of such composite metal oxides include LiCoO2, LiMn2O4, LiNiO2, LiCo 1-x Ni x O2(0.01 <x<1)、LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, LiNi 1 / 2 Mn 3 / 2 O4, etc., and these lithium composite oxides may be partially substituted with other elements, and a portion of the cobalt, manganese, and nickel may be partially substituted with at least one element such as B, Nb, Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn, Cu, Bi, Mo, and La, a portion of the O may be substituted with S or F, or a compound containing these other elements may be coated. Examples of lithium-containing olivine-type phosphates include LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, LiFe 1-x MxPO4 (M is at least one selected from Co, Ni, Mn, Cu, Zn, and Cd, and x is 0≦x≦0.5).

[0090] The conductive agent and binder for the positive electrode may be the same as those for the negative electrode. The positive electrode current collector may be, for example, aluminum, stainless steel, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. The surface of these materials may be oxidized, or the positive electrode current collector surface may be unevenly formed by surface treatment. The form of the current collector may be, for example, a sheet, a net, a foil, a film, a punched one, a lath body, a porous body, a foam, a fiber group, or a molded body of a nonwoven fabric.

[0091] <Nonaqueous electrolyte> The non-aqueous electrolyte is a non-aqueous solvent having an electrolyte salt dissolved therein. There are no particular limitations on the type of non-aqueous electrolyte, and various types can be used.

[0092] The electrolyte salt used is one that dissolves in a non-aqueous electrolyte, and examples of the electrolyte salt include inorganic lithium salts such as LiPF6, LiBF4, LiPO2F2, LiN(SO2F)2, and LiClO4; lithium salts containing a chain-like fluorinated alkyl group such as LiN(SO2CF3)2, LiN(SO2C2F5)2, LiCF3SO3, LiC(SO2CF3)3, LiPF4(CF3)2, LiPF3(C2F5)3, LiPF3(CF3)3, LiPF3(iso-C3F7)3, and LiPF5(iso-C3F7); lithium salts containing a cyclic fluorinated alkylene chain such as (CF2)2(SO2)2NLi and (CF2)3(SO2)2NLi; and lithium salts having an oxalate complex as the anion, such as lithium bis[oxalate-O,O']borate and lithium difluoro[oxalate-O,O']borate. Among these, particularly preferred electrolyte salts are LiPF6, LiBF4, LiPO2F2, and LiN(SO2F)2, and the most preferred electrolyte salt is LiPF6. These electrolyte salts can be used alone or in combination of two or more. In addition, a suitable combination of these electrolyte salts is preferably a combination containing LiPF6 and at least one lithium salt selected from LiBF4, LiPO2F2, and LiN(SO2F)2 in the non-aqueous electrolyte solution.

[0093] The concentration of all of these electrolyte salts dissolved in the nonaqueous solvent is usually preferably 0.3 M or more, more preferably 0.5 M or more, and even more preferably 0.7 M or more. The upper limit is preferably 2.5 M or less, more preferably 2.0 M or less, and even more preferably 1.5 M or less.

[0094] On the other hand, the non-aqueous solvent may be a cyclic carbonate, a chain carbonate, a chain ester, an ether, an amide, a phosphoric acid ester, a sulfone, a lactone, a nitrile, an S=O bond-containing compound, etc., and preferably contains a cyclic carbonate. The term "chain ester" is used as a concept including a chain carbonate and a chain carboxylate ester.

[0095] Examples of the cyclic carbonate include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 4-fluoro-1,3-dioxolan-2-one (FEC), trans- or cis-4,5-difluoro-1,3-dioxolan-2-one (hereinafter, both are collectively referred to as "DFEC"), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and 4-ethynyl-1,3-dioxolan-2-one (EEC). More preferred are at least one selected from ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 4-fluoro-1,3-dioxolan-2-one and 4-ethynyl-1,3-dioxolan-2-one (EEC) from the viewpoints of improving the charge rate characteristics of the power storage device and suppressing the amount of gas generated during high-temperature operation, and even more preferred are at least one cyclic carbonate having an alkylene chain selected from propylene carbonate, 1,2-butylene carbonate and 2,3-butylene carbonate. The proportion of the cyclic carbonate having an alkylene chain in all the cyclic carbonates is preferably 55% by volume to 100% by volume, and even more preferably 60% by volume to 90% by volume.

[0096] Therefore, the non-aqueous electrolyte is preferably prepared by dissolving an electrolyte salt containing at least one lithium salt selected from LiPF6, LiBF4, LiPO2F2, and LiN(SO2F)2 in a non-aqueous solvent containing one or more cyclic carbonates selected from ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 4-fluoro-1,3-dioxolan-2-one, and 4-ethynyl-1,3-dioxolan-2-one. The cyclic carbonate is more preferably one or more cyclic carbonates having an alkylene chain selected from propylene carbonate, 1,2-butylene carbonate, and 2,3-butylene carbonate.

[0097] In particular, it is preferable to use a non-aqueous electrolyte solution in which the concentration of the total electrolyte salt is 0.5M to 2.0M, the electrolyte salt contains at least LiPF6, and further contains at least one lithium salt selected from LiBF4, LiPO2F2, and LiN(SO2F)2 at 0.001M to 1M. If the ratio of lithium salts other than LiPF6 in the non-aqueous solvent is 0.001M or more, the effect of improving the charge rate characteristics of the power storage device and suppressing the amount of gas generation during high-temperature operation is easily exhibited, and if it is 1.0M or less, there is little concern that the effect of improving the charge rate characteristics of the power storage device and suppressing the amount of gas generation during high-temperature operation will decrease, which is preferable. The ratio of lithium salts other than LiPF6 in the non-aqueous solvent is preferably 0.01M or more, particularly preferably 0.03M or more, and most preferably 0.04M or more. The upper limit is preferably 0.8M or less, more preferably 0.6M or less, and particularly preferably 0.4M or less.

[0098] In addition, the non-aqueous solvent is preferably used in a mixed state in order to achieve appropriate physical properties. Examples of the combination include a combination of a cyclic carbonate and a chain carbonate, a combination of a cyclic carbonate, a chain carbonate and a lactone, a combination of a cyclic carbonate, a chain carbonate and an ether, a combination of a cyclic carbonate, a chain carbonate and a chain ester, a combination of a cyclic carbonate, a chain carbonate and a nitrile, and a combination of a cyclic carbonate, a chain carbonate and a compound containing an S=O bond.

[0099] Suitable examples of the chain ester include one or more asymmetric chain carbonates selected from methyl ethyl carbonate (MEC), methyl propyl carbonate (MPC), methyl isopropyl carbonate (MIPC), methyl butyl carbonate, and ethyl propyl carbonate; one or more symmetric chain carbonates selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, and dibutyl carbonate; pivalic acid esters such as methyl pivalate, ethyl pivalate, and propyl pivalate; and one or more chain carboxylate esters selected from methyl propionate, ethyl propionate, propyl propionate, methyl acetate, and ethyl acetate (EA).

[0100] Among the chain esters, chain esters having a methyl group selected from dimethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, methyl propionate, methyl acetate, and ethyl acetate (EA) are preferred, and chain carbonates having a methyl group are particularly preferred.

[0101] In addition, when chain carbonates are used, it is preferable to use two or more kinds. It is more preferable that both symmetric chain carbonates and asymmetric chain carbonates are contained, and it is even more preferable that the content of the symmetric chain carbonate is higher than that of the asymmetric chain carbonate.

[0102] The content of the chain ester is not particularly limited, but is preferably in the range of 60% by volume to 90% by volume relative to the total volume of the nonaqueous solvent. If the content is 60% by volume or more, the viscosity of the nonaqueous electrolyte does not become too high, and if the content is 90% by volume or less, the electrical conductivity of the nonaqueous electrolyte decreases, which reduces the improvement of the charge rate characteristics of the electricity storage device and the effect of suppressing the amount of gas generation during high-temperature operation, so the above range is preferable.

[0103] The volume ratio of the symmetric chain carbonate in the chain carbonate is preferably 51% by volume or more, more preferably 55% by volume or more. The upper limit is more preferably 95% by volume or less, and even more preferably 85% by volume or less. It is particularly preferable that the symmetric chain carbonate contains dimethyl carbonate. It is more preferable that the asymmetric chain carbonate has a methyl group, and methyl ethyl carbonate is particularly preferable. In the above case, the charging rate characteristic of the power storage device is improved and the effect of suppressing the amount of gas generation during high-temperature operation is improved, which is preferable.

[0104] From the viewpoint of improving the charge rate characteristics of the electricity storage device and increasing the effect of suppressing the amount of gas generated during high-temperature operation, the ratio of cyclic carbonate to chain ester (volume ratio) is preferably 10:90 to 45:55, more preferably 15:85 to 40:60, and particularly preferably 20:80 to 35:65.

[0105] <The structure of a lithium battery> The structure of the lithium battery of the present invention is not particularly limited, and examples include a coin battery having a positive electrode, a negative electrode, and a single-layer or multi-layer separator, and further, a cylindrical battery or a square battery having a positive electrode, a negative electrode, and a roll-shaped separator.

[0106] As the separator, an insulating thin film having a large ion permeability and a predetermined mechanical strength is used. Examples include polyethylene, polypropylene, cellulose paper, glass fiber paper, polyethylene terephthalate, and polyimide microporous membranes, and a multilayer film formed by combining two or more of them can also be used. In addition, the surface of these separators can be coated with resins such as PVDF, silicone resins, and rubber-based resins, or particles of metal oxides such as aluminum oxide, silicon dioxide, and magnesium oxide. The pore size of the separator may be within a range that is generally useful for batteries, for example, 0.01 μm to 10 μm. The thickness of the separator may be within a range that is generally useful for batteries, for example, 5 μm to 300 μm.

[0107] <Solid electrolyte> A solid electrolyte is a solid electrolyte that allows ions to move inside. In particular, inorganic solid electrolytes are solid in a stationary state, and therefore are not usually dissociated or liberated into cations and anions. Inorganic solid electrolytes are not particularly limited as long as they have the conductivity of metal ions belonging to Group 1 of the periodic table, and generally have almost no electronic conductivity. Representative examples of inorganic solid electrolytes include sulfide inorganic solid electrolytes and oxide inorganic solid electrolytes. In particular, sulfide solid electrolytes are preferably used because they have high ionic conductivity and can be formed into a dense molded body with few grain boundaries by simply applying pressure at room temperature.

[0108] The sulfide inorganic solid electrolyte may be amorphous glass, crystallized glass, or a crystalline material. Specific examples of the sulfide inorganic solid electrolyte include, but are not limited to, the following combinations. Li2S-P2S5, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S -GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li 10 GeP2S 12 .

[0109] Among the above combinations, the LPS glass produced by combining Li2S-P2S5 Preferred examples of sulfide inorganic solid electrolytes other than those mentioned above include argerodite-type solid electrolytes such as Li6PS5Cl and Li6PS5Br.

[0110] Oxide-based inorganic solid electrolytes contain oxygen atoms and are made of metals that belong to Group 1 of the periodic table. It is preferable that the material has both on-conductivity and electronic insulation properties.

[0111] As the oxide inorganic solid electrolyte, for example, Li having a LISICON (Lithium super ionic conductor) type crystal structure is used. 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li7La3Zr2O with garnet-type crystal structure 12 (LLZ), lithium phosphate (Li3PO4), LiPON, in which some of the oxygen in lithium phosphate is replaced with nitrogen, Li3BO3-Li2SO4, Li2O-B2O3-P2O5, Li2O-SiO2, or Li6BaLa2Ta2O 12 etc. are preferred.

[0112] The volume average particle diameter of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less. EXAMPLES

[0113] Next, the present invention will be described in more detail with reference to examples and comparative examples. However, the present invention is not limited to the following examples and includes various combinations that can be easily inferred from the gist of the invention.

[0114] [Example 1-1] <Raw material preparation process> Li2CO3 (average particle size 4.6 μm) and anatase type TiO2 (specific surface area 10 m2) were mixed so that the atomic ratio of Li to Ti (Li / Ti) was 0.83. 2 The raw material powder was weighed out (100g / g), and ion-exchanged water was added to the raw material powder so that the solid content of the slurry was 41% by mass, and the mixture was stirred to prepare a raw material mixed slurry. The raw material mixed slurry was wet-mixed and pulverized using a bead mill (Willi & Bachofen, model: Dyno Mill KD-20BC, agitator material: polyurethane, vessel inner surface material: zirconia) in which zirconia beads (outer diameter: 0.65 mm) were filled to 80% by volume in a vessel, with the agitator peripheral speed at 13 m / s, the slurry feed rate at 55 kg / hr, and the vessel inner pressure controlled to 0.02 to 0.03 MPa.

[0115] <Firing process> The obtained mixed slurry was introduced into the furnace core tube from the raw material supply side of the furnace using a rotary kiln-type firing furnace (furnace core tube length: 4 m, furnace core tube diameter: 30 cm, external heating type) equipped with an adhesion prevention mechanism, and dried and fired in a nitrogen atmosphere. At this time, the inclination angle of the furnace core tube from the horizontal direction was 2.5 degrees, the rotation speed of the furnace core tube was 20 rpm, the flow rate of nitrogen introduced into the furnace core tube from the fired product recovery side was 20 L / min, the heating temperatures of the furnace core tube were 600°C on the raw material supply side, 880°C in the center, and 880°C on the fired product recovery side, and the firing product was held at 880°C for 30 minutes.

[0116] <Post-processing process> The sintered material collected from the sintered material collection side of the furnace tube was pulverized using a hammer mill (Dalton, AIIW-5 type) under the conditions of screen opening: 0.5 mm, rotation speed: 8,000 rpm, and powder feed rate: 25 kg / hr.

[0117] <Surface treatment process> The crushed calcined powder was mixed with ion-exchanged water so that the solid content of the slurry was 40% by mass, and then 2.75 mmol of lithium molybdate (Li2MoO4) as treatment agent 1 and 5.08 mmol of aluminum sulfate 16-hydrate (Al2(SO4)3·16H2O) as treatment agent 2 were added to 100 g of the crushed calcined powder to prepare a mixed slurry. This mixed slurry was sprayed and dried at an atomizer speed of 25,000 rpm and a drying temperature of 235°C using a spray dryer (L-8i manufactured by Okawara Kakoki Co., Ltd.) and granulated. The powder that passed through the sieve was then placed in an alumina sagger and heat-treated at 500°C for 1 hour in a mesh belt conveying continuous furnace equipped with a collection box at the outlet, where the temperature was controlled to be 25°C and the dew point was controlled to be below -20°C. The heat-treated powder was cooled in the recovery box and classified using a sieve (screen opening: 53 μm). The powder that passed through the sieve was collected in an aluminum laminate bag and sealed, and then removed from the recovery box to produce lithium titanate powder.

[0118] [Comparative Example 1-1] Lithium titanate powder was produced in the same manner as in Example 1 except that in the sintering process, the heating temperatures of the furnace tube were 840°C in the center and 840°C on the sintered product recovery side, the holding time of the sintered product at 840°C was 30 minutes, and in the surface treatment process, treatment agent 1 was not added, but aluminum sulfate 16-hydrate (Al2(SO4)3·16H2O) was added as treatment agent 2 as shown in Table 1.

[0119] [Comparative Example 1-2] In the sintering process, the heating temperature of the furnace tube was 840°C in the center and 840°C on the sintered product recovery side, the sintered product was held at 840°C for 30 minutes, and aluminum sulfate hexahydrate (Al2(SO4)3·16H2O) was added as shown in Table 1. Except for this, lithium titanate powder was produced in the same manner as in Example 1-1.

[0120] [Comparative Example 1-3] A lithium titanate powder was produced in the same manner as in Comparative Example 1-2, except that neither Treatment Agent 1 nor Treatment Agent 2 was added in the surface treatment step.

[0121] [Measuring the content of metal elements] The contents of metal elements contained in the lithium titanate powders of Examples 1-1, 2-1 to 2-5 and Comparative Examples 1-1 to 1-3, and 2-1 to 2-3 (hereinafter sometimes referred to as the lithium titanate powders of each Example or Comparative Example) were measured as follows.

[0122] <X-ray fluorescence analysis (XRF): Identification of molybdenum, aluminum, and impurity content> Using an X-ray fluorescence spectrometer (manufactured by SII Technology Co., Ltd., product name "SPS5100"), the elements contained in the lithium titanate powder of each Example and Comparative Example were quantitatively analyzed. The measurement sample was prepared by filling a precisely weighed sample with nitric acid and hydrofluoric acid, sealing it, irradiating it with microwaves to heat decompose it, and then adding ultrapure water to a constant volume to use as the test liquid. The amount of metal impurities was calculated from the mass ratio of the content of the elements obtained by ICP-AES. The amount of metal impurities was the total content of iron (Fe), chromium (Cr), and nickel (Ni).

[0123] [Measurement of powder properties] Various physical properties of the lithium titanate powders of the respective Examples and Comparative Examples were measured as follows.

[0124] <Measurement of specific surface area> The specific surface area (m 2 / g) is fully automatic A BET specific surface area measuring device (manufactured by Mountec Co., Ltd., product name "Macsorb HM model-1208") was used, and nitrogen gas was used as the adsorption gas. 0.5 g of the measurement sample powder was weighed out and placed in a φ12 standard cell (HM1201-031), and after degassing for 0.5 hours under vacuum at 100°C, the measurement was performed by the BET single point method.

[0125] <Calculation of D50 of primary and secondary particles: Dry laser diffraction scattering method> The D50 of the lithium titanate powder of each example and comparative example was calculated from the particle size distribution curve measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII, manufactured by Nikkiso Co., Ltd.). 50 mg of the sample was put into a container containing 50 ml of ion-exchanged water as the measurement solvent, and the container was shaken by hand until it was visually confirmed that the powder was uniformly dispersed in the measurement solvent. Then the container was placed in the measurement cell for measurement. For the crushing treatment, ultrasonic waves (30 W, 3 s) were applied using the ultrasonic wave generator inside the apparatus. Further, the measurement solvent was added until the transmittance of the slurry was within the appropriate range (the range indicated by the green bar of the apparatus) for particle size distribution measurement. The D50 of the mixed powder before and after crushing was calculated from the obtained particle size distribution curve. Note that the D50 before crushing corresponds to the D50 of the secondary particles, and the D50 after crushing corresponds to the D50 of the primary particles.

[0126] <Measurement of 1-methyl-2-pyrrolidone oil absorption> The 1-methyl-2-pyrrolidone oil absorption of the lithium titanate powder of each example and comparative example was measured using an Absorptometer C (manufactured by Brabender). 20 g of the lithium titanate powder was weighed and put into the apparatus casing. After rotating the stirring blade to make it uniform, 1-methyl-2-pyrrolidone was added at a dropping rate of 4.0 ml / min while rotating at 125 rpm, and then the automatic operation was started. After the torque increased and then decreased, the measurement was terminated when the torque value reached 0 mNm. The oil absorption corresponding to the maximum torque value was measured by reading it from the obtained graph.

[0127] <Measurement of pH> The pH of the lithium titanate powder of each example and comparative example was measured using a pH meter D-51 (manufactured by Horiba, Ltd.). A mixed solution was prepared by putting 5.0 g of the lithium titanate powder and 45.0 g of pure water in a nitrogen atmosphere. After stirring for 5 minutes at a liquid temperature of 25 °C, the pH of this mixed solution was measured.

[0128] <X-ray diffraction measurement> X-ray diffraction measurements were performed on the lithium titanate powders of each of the Examples and Comparative Examples. An X-ray diffractometer using CuKα radiation (MiniFlex600 model, manufactured by Rigaku Corporation) was used as the measuring device. The measurement conditions for the X-ray diffraction measurements were as follows: measurement angle range (2θ): 10° to 90°, step interval: 0.01°, measurement time: 0.25 seconds / step, radiation source: CuKα radiation, tube voltage: 40 V, current: 15 mA. The structure was refined by Rietveld refinement to obtain Li4Ti5O 12 The other crystalline components are Li 0.6 Ti 3.4 Checked for the presence of O8.

[0129] [Evaluation of battery characteristics] Coin-type batteries were fabricated using the lithium titanate powders of each of the Examples and Comparative Examples, and their battery characteristics were evaluated. The evaluation results are shown in Tables 1 and 3.

[0130] <Preparation of negative electrode sheet> The negative electrode sheet was prepared as follows in a room controlled at room temperature of 25°C and a dew point of -20°C or less. The lithium titanate powder of each example was taken out of the aluminum laminate bag in a room controlled at a temperature of 25°C and a dew point of -20°C or less. The lithium titanate powder of each example taken out was mixed as follows in a ratio of 90% by mass as an active material, 5% by mass of acetylene black as a conductive agent, and 5% by mass of polyvinylidene fluoride as a binder to prepare a paint. Polyvinylidene fluoride, acetylene black, and 1-methyl-2-pyrrolidone dissolved in 1-methyl-2-pyrrolidone in advance were mixed in a planetary stirring and defoaming device, and then lithium titanate powder was added, and the total solid concentration was adjusted to 64% by mass, and mixed in a planetary stirring and defoaming device. Then, 1-methyl-2-pyrrolidone was added, and the total solid concentration was adjusted to 50% by mass, and mixed in a planetary stirring and defoaming device to prepare a paint. The obtained coating material was applied onto an aluminum foil and dried to prepare a single-sided negative electrode sheet for a coin battery described later and a double-sided negative electrode sheet for a laminate battery described later. The target coating weight was 7.5 mg / cm2. 2 It was decided.

[0131] <Measurement of electrode density> The negative electrode single-sided sheet coated as described above was pressed with a roll press (roll φ60×150 mm, equivalent to a press pressure of 40 MPa), and the density of the active material layer was measured as the "electrode density." The evaluation results are shown in Table 1. A high electrode density is preferable because it allows more active material to be packed into a given volume, which results in an increased capacity that can be used as a battery.

[0132] <Preparation of positive electrode sheet> A positive electrode single-sided sheet was prepared in the same manner as described in <Preparation of Negative Electrode Sheet> above, including the ratios of the active material, conductive agent, and binder, except that lithium nickel cobalt manganese oxide powder was used as the active material.

[0133] <Preparation of electrolyte> The electrolyte used in the battery for characteristic evaluation was prepared as follows. In an argon glove box controlled at a temperature of 25°C and a dew point of -70°C or less, a non-aqueous solvent of ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:2 (volume ratio) was prepared, and LiPF6 was dissolved in this as an electrolyte salt to a concentration of 1M to prepare the electrolyte for the coin battery described below. Similarly, a non-aqueous solvent of propylene carbonate (PC): diethyl carbonate (DEC) = 1:2 (volume ratio) was prepared, and LiPF6 was dissolved in this as an electrolyte salt to a concentration of 1.3M to prepare the electrolyte for the laminate battery described below.

[0134] <Preparation of coin battery> The negative electrode sheet prepared by the above method was punched into a circle with a diameter of 14 mm and a thickness of 2 t / cm 2 The electrode was pressed at a pressure of 1000 MPa and then vacuum dried at 120° C. for 5 hours to prepare an electrode for evaluation. The electrode for evaluation and metallic lithium (formed into a circle with a thickness of 0.5 mm and a diameter of 16 mm) were placed opposite each other via glass filters (one each of ADVANTEC GA-100 and Whatman GF / C), and the nonaqueous electrolyte prepared by the method described above in <Preparation of electrolyte> was added and sealed to prepare a 2032-type coin battery.

[0135] <Preparation of laminated battery> The laminated battery was fabricated in a room controlled at a room temperature of 25° C. and a dew point of −40° C. or less as follows. 2 The positive electrode double-sided sheet was pressed at a pressure of 2t / cm to prepare a negative electrode having a lead wire connection portion. 2 After pressing at a pressure of 1000 kPa, a positive electrode with a lead wire connection was produced. The produced negative and positive electrodes were vacuum dried at 150°C for 12 hours. The vacuum dried positive and negative electrodes were laminated facing each other with a separator (UPZ210, manufactured by Ube Industries) between them, and aluminum foil lead wires were connected to the positive and negative electrodes, respectively. The laminated battery electrolyte prepared by the method described above in <Preparation of electrolyte> was added, and the laminated battery was vacuum sealed with aluminum laminate to produce a laminated battery for evaluation. The capacity of the battery was 350mAh, and the ratio of the negative and positive electrode capacities (negative electrode capacity / positive electrode capacity) was 1.2.

[0136] <Measurements of initial discharge capacity, volumetric energy density, and rate characteristics> The coin-type battery prepared by the method described in the above <Preparation of Coin Battery> was placed in a thermostatic chamber at 25°C and charged at 0.2 mA / cm in the direction in which Li was absorbed in the evaluation electrode. 2 The battery was charged to 1 V at a current density of 0.05 mA / cm at 1 V. 2 After constant current and constant voltage charging, the battery was charged to a current density of 0.2 mA / cm 2 A constant current discharge was performed for three cycles, discharging to 2V at a current density of 10 ... For example, 1C refers to the current value that can fully discharge (or fully charge) the theoretical capacity in 1 / 1 hour, and 0.1C refers to the current value that can fully discharge (or fully charge) the theoretical capacity in 1 / 0.1 hour.

[0137] <Measurement of gas generation amount after 50 cycles at 60℃> In a thermostatic chamber at 25°C, the laminated battery prepared by the method described above in <Preparation of Laminated Battery> was charged to 2.75 V at a current of 0.2 C, and then subjected to constant current and constant voltage charging at 2.75 V until the charging current became 0.05 C, after which constant current discharging was repeated for three cycles at a current of 0.2 C to 1.4 V. The volume of the laminated battery was then measured by the Archimedes method, and this was taken as the initial volume of the laminated battery (hereinafter sometimes referred to as the initial volume).

[0138] Next, in a thermostatic chamber at 60°C, the battery was charged to 2.75 V at a current of 1 C, and then further charged at 2.75 V until the charging current became 0.05 C. A cycle test was then performed in which this was repeated 50 cycles of constant current discharge at a current of 1 C to 1.4 V.

[0139] After 50 cycles of the cycle test, the volume of the laminated battery was measured by Archimedes' method, and was taken as the volume of the laminated battery after the cycle test (hereinafter, sometimes referred to as the volume after the cycle test). The amount of gas generated (ml) was calculated by subtracting the initial volume from the volume after the cycle test, and converted to the amount of gas generated (ml / Ah) after 50 cycle tests. The relative values ​​when the amount of gas generated in Comparative Example 1-2 was taken as 100% are shown in Table 1. (In this specification, it may be referred to as the amount of gas generated (%) at 60°C cycle.)

[0140] <Measurement of battery resistance after long-term storage at 60℃> A laminated battery prepared by the method described above in <Preparation of Laminated Battery> was charged to 2.75 V at a current of 0.2 C in a thermostatic chamber at 25°C, and then subjected to a storage test for 30 days in a thermostatic chamber at 60°C. After the storage test was completed, the battery was removed and AC impedance was measured in a thermostatic chamber at 25°C. The resistance value (Ω) corresponding to a frequency of 1 kHz was read. The relative values, with the resistance value after storage in Comparative Example 1-2 taken as 100%, are shown in Table 1. (In this specification, this may be referred to as resistance value % after storage at 60°C.)

[0141] [Table 1]

[0142] <Evaluation Results> The electrode using the lithium titanate powder of Example 1-1 was excellent in initial discharge capacity, rate characteristics, electrode density, and volume energy density, and furthermore, it was possible to significantly suppress the gas generation amount and the increase in resistance value during high-temperature operation. On the other hand, when using lithium titanate powder synthesized by the same production method as in Example 1-1 but not containing both molybdenum and aluminum on the surface (Comparative Examples 1-1 and 1-3), the gas generation amount and the resistance value during high-temperature operation increased. Also, when using lithium titanate powder that contains molybdenum and aluminum on the surface but is synthesized by a production method different from that of Example 1-1 and has an NMP oil absorption amount greater than 71 mL / 100 g (Comparative Example 1-2), the electrode density became small and the volume energy density became low. From these results, it was found that lithium titanate containing molybdenum and aluminum and showing a specific NMP oil absorption amount exhibits particularly good battery characteristics. It is presumed that the performance was greatly improved by the change in the oil absorption amount reflecting the change in the surface state, rather than depending only on the D50 of the primary particles and the D50 of the secondary particles.

[0143] <Results of X-ray photoelectron spectroscopy (XPS) analysis> Regarding the lithium titanate powders of Example 1-1 and Comparative Example 1-2, the valence distribution of Mo present on the surface of the primary particles was measured using a PHI5000 scanning X-ray photoelectron spectrometer manufactured by ULVAC-PHI, Inc. After sampling each sample on an Al plate, measurements were carried out using an X-ray source of AlKα (monochromatic, 1486.6 eV, 50 W), an analysis area of 200 μmφ, and utilizing a charge neutralization mechanism (electron gun + Ar ion). The results of peak separation calculation (using a peak separation program on MATLAB (registered trademark)) for the obtained Mo3d spectra are shown below.

[0144]

Table 2

[0145] Regarding the lithium titanate powders of Example 1-1 and Comparative Example 1-2, Mo 6+ , Mo 5+ , Mo 4+ It was confirmed that there was a difference in the valence distribution ratio of Mo. Figure 1 shows an example of peak separation related to the Mo valence distribution.

[0146] [Effect of manufacturing process conditions on lithium titanate powder] [Examples 2-1 to 2-5, Comparative Examples 2-1 to 2-3] A lithium titanate powder was produced in the same manner as in Example 1-1, except that the raw material preparation, surface treatment step, and secondary particle formation step were carried out under the conditions shown in Table 3.

[0147] [Table 3]

[0148] <Evaluation Results> The electrodes using the lithium titanate powders of Examples 2-1 to 2-5 contain molybdenum and aluminum on the surface, and by controlling the 1-methyl-2-pyrrolidone oil absorption within a specific range, it was found that there is a tendency for the electrode density, initial discharge capacity, volumetric energy density, and rate characteristics to be improved and the battery characteristics to be maintained. On the other hand, the lithium titanate powders of Comparative Examples 2-1 to 2-3 exhibited characteristics of low electrode density and did not achieve an improvement in volumetric energy density. In particular, the specific surface area of ​​6.1 m 2 / g or less, D50 of the primary particles is 0.7 μm or more, and D50 of the secondary particles is 11 μm or more. The long-term characteristics of the batteries of Examples 2-1 to 2-5 showed the same tendency as that of Example 1-1. [Industrial Applicability]

[0149] The lithium titanate powder obtained by the present invention is useful as an electrode active material for lithium ion secondary batteries, since it can improve the electrode density and volumetric energy density and suppress the amount of gas generation and the increase in resistance value during high-temperature operation. Furthermore, lithium ion secondary batteries using this lithium titanate as an electrode active material are capable of stable, high-speed charging and discharging, and are therefore useful as power storage devices such as secondary batteries for driving or backing up various devices such as automobiles and electronic devices, and for storing power at night in homes and offices, etc.< / ph>

Claims

1. Li 4 Ti 5 O 12 The lithium titanate powder is mainly composed of the above lithium titanate, and is characterized in that the lithium titanate powder contains primary particles and secondary particles of lithium titanate, has a 1-methyl-2-pyrrolidone oil absorption of 57 mL / 100 g to 71 mL / 100 g, and has molybdenum (Mo) and aluminum (Al) present on the surfaces of the primary particles.

2. The lithium titanate powder has a specific surface area of ​​6.1 m 2 2. The lithium titanate powder according to claim 1, wherein the lithium titanate powder has a molecular weight of 1:1 or less.

3. 3. The lithium titanate powder according to claim 1, wherein the particle size D50 of primary particles corresponding to a cumulative volume of 50% in a volume-based particle size distribution measured by a laser diffraction scattering method is 0.7 μm or more.

4. The lithium titanate powder according to any one of claims 1 to 3, characterized in that the particle size D50 of secondary particles corresponding to a volume cumulative 50% in a volume-based particle size distribution measured by a laser diffraction scattering method is 11 µm or more.

5. An electrode sheet comprising the lithium titanate powder according to any one of claims 1 to 4.

6. An electricity storage device comprising the electrode sheet according to claim 5 .

Citation Information

Patent Citations

  • Modified lithium titanate composite material, preparation method and application thereof

    CN104979542A

  • Shape-controllable nano lithium titanate composite and preparation method thereof and lithium ion battery

    CN105870437A

  • Lithium-titanium multiple oxide, its manufacturing method and its use

    JP2001192208A

  • Method for producing porous lithium titanate, the porous lithium titanate and lithium battery using the same

    JP2012012261A

  • Lithium titanate precursor powder and manufacturing method thereof, manufacturing method of lithium titanate therewith, and lithium titanate, and electrode and electricity storage device therewith

    JP2017178688A